Biological Control of Aphis gossypii on Red Chili Pepper using Locally Isolated Beauveria bassiana and Metarhizium anisopliae - Dang Khoa Bui; Hidrayani Hidrayani; Nurbailis Nurbailis (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2025)
Red chili pepper (Capsicum annuum) is a high-value horticultural crop in Indonesia, but its production is severely constrained by Aphis gossypii, which can cause yield losses of up to 65%. This study aimed to evaluate the biological characteristics, virulence, and lethal-sublethal effects of local isolates of Beauveria bassiana and Metarhizium anisopliae against A. gossypii. Fungal viability and growth were assessed through spore germination and radial growth assays, while pathogenicity was evaluated using four conidial concentrations (10⁴–10¹⁰ conidia mL⁻¹). Aphid mortality, lethal concentration (LC), lethal time (LT), and reproductive performance were recorded, and the data were analyzed using factorial and probit analyses. The results showed that both fungi exhibited high spore viability (>96%) and stable mycelial growth rates (3.71–3.74 mm day⁻¹). Aphid mortality increased significantly with increasing conidial concentration, reaching 100% at 10¹⁰ conidia mL⁻¹, whereas mortality at 10⁴ conidia mL⁻¹ ranged from 26.67% to 40.00%. Probit analysis revealed comparable virulence, with LC₉₅ values of 8.09 for M. anisopliae and 8.29 for B. bassiana. Lethal time analysis showed a concentration-dependent killing pattern, with B. bassiana acting more rapidly at lower concentrations (10⁴–10⁶ conidia mL⁻¹) and M. anisopliae exhibiting shorter LT₅₀ values at higher concentrations (10⁸–10¹⁰ conidia mL⁻¹). In addition to lethal effects, both fungi significantly suppressed aphid reproduction, particularly at higher conidial concentrations. These findings demonstrate that B. bassiana and M. anisopliae possess strong and complementary bioefficacy against A. gossypii, supporting their potential application in integrated pest management programs.